Demonstration of two allelic forms of the bovine T cell antigen Bo5 (CD5) and studies of their inheritance - Howard, C.J.; Morrison, W. Ivan; Brown, W.C.; Naessens, Jan; Sopp, P. (Wiley, 1989)
Summary. Two monoclonal antibodies (mAbs), CC17 and IL‐A67, which are specific for the bovine equivalent of the CD5 antigen, Bo5, were each found to react with the cells of some animals but not others. The cattle tested were all positive for one or both of the mAbs, but the level of expression on cells expressing both determinants was slightly lower than that on cells expressing either of the determinants on their own. Both mAbs precipitated an antigen of 67kD. However, sequential immunoprecipitation experiments with cells that reacted with both mAbs demonstrated that the determinants are present on two different sets of molecules. These findings suggested that the mAbs recognize two co‐dominantly expressed allelic forms of Bo5. This was confirmed in family studies, with groups of full‐ and half‐sibling offspring of sires and dams of defined phenotypes. These experiments also showed that the gene encoding the Bo5 antigen is not linked to the major histo‐compatibility complex (MHC). The frequencies of the two alleles, which have been designated Bo5.1 and Bo5.2, in the cattle populations tested were 100% and 0%, respectively, in Bos taurus, and 10% and 90%, respectively, in Bos indicus.